Impulse for animal welfare outside the experiment. (April 2020) - Lewejohann, Lars; Schwabe, Kerstin; Häger, Christine; Jirkof, Paulin
Animal welfare is a growing societal concern and the well-being of animals used for experimental purposes is under particular scrutiny. The vast majority of laboratory animals are mice living in small cages that do not offer very much variety. Moreover, the experimental procedure often takes very little time compared to the time these animals have been bred to the desired age or are being held available for animal experimentation. However, for the assessment of animal welfare, the time spent waiting for an experiment or the time spent after finishing an experiment has also to be taken into account. In addition to experimental animals, many additional animals (e.g. for breeding and maintenance of genetic lines, surplus animals) are related to animal experimentation and usually face similar living conditions. Therefore, in terms of improving the overall welfare of laboratory animals, there is not only a need for refinement of experimental conditions but especially for improving living conditions outside the experiment. The improvement of animal welfare thus depends to a large extent on the housing and maintenance conditions of all animals related to experimentation. Given the current state of animal welfare research there is indeed a great potential for improving the overall welfare of laboratory animals.